Ethnomedicinal Study in Mekarbuana Village, Karawang District, Indonesia - Sri Gunarti, Neni; Fikayuniar, Lia; Edison, Acep (International Journal of Psychosocial Rehabilitation, 2020)
The local people from Mekarbuana, Tegalwaru Karawang is one of the people in Indonesia that still uses plants and animals as ingredients of traditional medicine. This study aimed to find out the natural ingredients that are used in the lives of local people in Mekarbuana including the parts used, how to use and how to process them. This research was carried out by snowball sampling method which was carried out in series by interview to the people who have been know about medicinal plants. Results of the study showed that 56 species of medicinal plants and 6 species of animals used by by local people for treatment with the most widely used parts of the plant namely leaves (58.92%). The part of the animal that is often used is meat (50%). For plants, the most commonly used method of processing is boiled (50%) and the most commonly used method of use is by drinking (60.71%). For animasl, the most commonly used method of processing is dried and packed (66.67%) and the most commonly used method of use is by eating (83.34%).